APPLICATION FOR DIAGNOSTIC DENTAL AND MOUTH DISEASE USING FORWARD CHAINING METHOD - Eko Siswanto; Ahmad Ashifuddin Aqham; Toni Wijanarko Adi Putra (UNIVERSITAS STEKOM, 2022)
The mouth is the entrance to the digestive system and contains accessory organs that are in the early stages of digestion, while teeth are made of a very hard material, namely dentin. (Indah Irma & Ayu Intan, 2013. Many people complain of pain in the teeth and mouth due to lack of hygiene in maintaining the health of this organ. So when people are attacked by dental and oral diseases, people try to do their own treatment, for example buying toothache medicine in the shop. According to Turban (in Vincent, 2011) an expert system is a system that uses human knowledge where this knowledge is entered into a computer and then used to solve problems that usually require human expertise or expertise. The method used is the forward chaining method, namely forward chaining starting from a set of facts (there are) by looking for rules that match the assumptions/hypotheses that exist towards conclusions (Siswanto 2010).